The concept of a function among prospective teachers - Martinho, Maria Helena (2019)
The study of functions is an important topic in the mathematics curriculum, relevant for the development of abstract thinking, the application of mathematics to everyday situations and the relationship with other domains of knowledge. However, often students do not have a satisfactory understanding of the function. This may be due to several factors, including the different conceptions of function that teachers themselves may have. As trainers of teachers, we investigate which notions of a function prospective teachers hold. The research conducted was qualitative, based on a questionnaire. The relevance of the topic, either from a mathematical or a didactical perspective, entails the need for designing new dynamics in teachers' education that are able to challenge intuitive conceptions and buil proper connections.